Dinamika Arsitektur Rumah Adat di Kabupaten Sumba Tengah - Nyoman Arisanti; Nyoman Rema; I Gustri Ngurah Jayanti; Philipus Jeraman (Badan Riset dan Inovasi Nasional (BRIN), 2022)
Marapu is the Sumba people's ancestral faith that believes in the power of the ancestors. The indigenous community in Central Sumba strongly embraces the traditional ceremonies related to the marapu faith. On the other hand, modernity, loaded with capitalistic values, opens up the possibility for mobilities, one of which is ideological mobility. Globalization, followed by the entrance of modern religions, creates technological shifts in the traditional community's cultural system. This research investigates the dynamics of the traditionals houses architecture in Central Sumba Regency. This research also scrutinizes the ideology and other factors underlying the shifts. The theories of ideology and hegemony are eclectically applied. This research employs a qualitative research design. Data are collected through field surveys conducted in the traditional villages. Next, village members, relevant stakeholders are also interviewed. Besides that, a literature study is conducted, followed by a descriptive-qualitative analysis. The material and functional shifts of the traditional house happen due to the rise of new ideologies, hegemony imposed by the government, and economic factors. The shifts resulting from social and cultural changes are hopefully in line with the efforts to preserve the traditions and cultural remains of the traditional villages.